The quality of life of hemodialysis patients in Yogyakarta, Indonesia - Siswandi, Siswandi; Perwitasari, Dyah Aryani; B Simanjuntak, Lamhot; Suhendra, Gugun; Wulandari, Dewi; Dania, Haafizah; Faridah, Imaniar Noor; Adnan, Adnan (Pharmaciana, 2024)
The assessment of quality of life serves as a critical evaluation of the effectiveness of the administered hemodialysis treatment. The measurement of quality of life can be conducted using the Kidney Disease Quality of Life Short Form (KDQoL-SF™) questionnaire. This research aims to gather information concerning the quality of life among patients with hemodialysis due to chronic kidney failure at the dr. S. Hardjolukito Regional Military Hospital in Yogyakarta. The research employed a cross-sectional design. The respondents consisted of 65 patients selected through purposive sampling based on specific inclusion and exclusion criteria. The Independent T-test, Mann-Whitney test, Chi-Square test and Fischer test were conducted to define the association between quality of life and respondent characteristics. Most of the hemodialysis patients was male (50.8%) with average od age was 54.66 years old. The findings revealed that 64.6% of the respondents experienced moderate/poor quality of life, while 35.4% exhibited good quality of life. Statistical analysis established a significant relationship between respondent characteristics and quality of life based on the variables of age and duration of hemodialysis (p<0.05). Hemoglobin levels, number of prescribed medications, gender, education, occupation and income demonstrated no significant relationship with the quality of life. Among the respondents’ characteristics, age and duration of hemodialysis were associated with the quality of life.